From the Basis of Epimorphic Regeneration to Enhanced Regenerative Therapies - Laplace-Builhé, Béryl; Bahraoui, Sarah; Jorgensen, Christian; Djouad, Farida (Frontiers in Cell and Developmental Biology, 2021)
Current cell-based therapies to treat degenerative diseases such as osteoarthritis (OA) fail to offer long term beneficial effects. The therapeutic effects provided by mesenchymal stem cell (MSC) injection, characterized by a reduced pain and an improved functional activity in patients with knee OA, are reported at short-term follow-up since the improved outcomes plateau or, even worse, decline several months after MSC administration. This review tackles the limitations of MSC-based therapy for degenerative diseases and highlights the lessons learned from regenerative species to comprehend the coordination of molecular and cellular events critical for complex regeneration processes. We discuss, how MSC injection generates a positive cascade of events resulting in a long-lasting systemic immune regulation with limited beneficial effects on tissue regeneration while in regenerative species fine-tuned inflammation is required for progenitor cell proliferation, differentiation and regeneration. Finally, we stress the direct or indirect involvement of cells derived from neural crest cells (NCC) in most if not all adult regenerative models studied so far. Since, NCC form niches in distinct mammalian adult tissues we emphasize that they might suffer from a developmental loss of their capacity to induce intrinsic regenerative potential or a repressive effect of their microenvironment that could be unlocked or counteracted to permit regeneration in adult mammalian.